"ISOLATED" DIASTOLIC MYOCARDIAL DYSFUNCTION IN DIABETES MELLITUS - Kamolova Zarina Zokhidovna; Gafforov Xudoyor Xudoyberdiyevich (Journals Park Publishing, 2022)
Usually, the presence of a low ejection fraction (LV) of the left ventricle (LV) clearly explains the clinical picture of chronic heart failure (CHF). However, recently there has been an increase in the number of patients with CHF clinic against the background of normal LV LV (>50%). Most often, these are elderly women with arterial hypertension (AH), prone to the sudden development of acute left ventricular failure with a clinical picture of pulmonary edema. In such patients, diastolic dysfunction (DD) of the myocardium is especially often found against the background of preserved LV LV. It is proved that the myocardium in the diastole is more sensitive to ischemia and the presence of DD earlier and more accurately indicates the pathology of the myocardium.
Keywords: diabetes mellitus, arterial hypertension, chronic heart failure, diastolic dysfunction.